1983
DOI: 10.1071/bt9830411
|View full text |Cite
|
Sign up to set email alerts
|

The study of plant phylogeny using amino acid sequences of Ribulose-1,5-Bisphosphate Carboxylase. II. The analysis of small subunit data to form phylognetic trees.

Abstract: The first 40 amino acid sequences of the small subunit of ribulose bisphosphate carboxylase are given for 24 angiosperm species, three from each of eight families chosen because cytochrome c and plastocyanin sequences are already available. Using computer methods, these data have been analysed to yield minimal phylogenetic Steiner trees. A well defined minimal tree becomes apparent when data from all three proteins are combined. The root of the minimal tree is indicated by the node where a gymnosperm joins. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…One might therefore expect high levels of homoplasy in neutral molecular characters given a sufficient amount of time. Archie (1989b) has shown that the consistency indices of two plant nucleotide data sets (derived by Bremer, 1988, from the amino acid studies of Martin et al, 1983Martin et al, , 1985 do not differ from those expected in randomly generated data, perhaps indicating near saturation with homoplastic multiple hits.…”
Section: Homoplasy and Selectionmentioning
confidence: 98%
“…One might therefore expect high levels of homoplasy in neutral molecular characters given a sufficient amount of time. Archie (1989b) has shown that the consistency indices of two plant nucleotide data sets (derived by Bremer, 1988, from the amino acid studies of Martin et al, 1983Martin et al, , 1985 do not differ from those expected in randomly generated data, perhaps indicating near saturation with homoplastic multiple hits.…”
Section: Homoplasy and Selectionmentioning
confidence: 98%
“…If these data are reliable, a much needed general framework of angiosperm phylogeny could be generated. Most protein sequence data used in phylogenetic reconstruction come from the small subunit of ribulose biphosphate carboxylase (RBC-SSU; Martin et al, 1983;Martin and Dowd, 1984a, 1984b, 1984c, p1astocyanin (Boulter et al, 1979), and cytochrome c (Boulter et al, 1972). Sometimes the phylogenetic trees generated from sequences in these different proteins are inconsistent, and there is uncertainty about the stability of the data.…”
mentioning
confidence: 99%
“…A major problem is that the number of variable amino acid positions currently available in a single protein (15-30) is generally too small for a well supported hypothesis about the interrelationships of the taxa investigated (Peacock, 1981). The combination of data from several species into familial sequences (Martin et al, 1983) and the subsequent combination offamilial sequences from several proteins (Martin et al, 1985) yield data sets with a larger number of informative amino acid positions. Such data sets may become large enough to say something about the interrelationships of the angiosperm families included.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One might therefore expect high levels of homoplasy in neutral molecular characters given a sufficient amount of time. Archie (1989b) has shown that the consistency indices of two plant nucleotide data sets (derived by , from the amino acid studies of Martin et al, 1983Martin et al, , 1985 do not differ from those expected in randomly generated data, perhaps indicating near saturation with homoplastic multiple hits.…”
Section: Homoplasy and Selectionmentioning
confidence: 97%